The problem of bilingualism and bilingual education in the context of the development of the modern world, given the sociolinguistic studios of Alexander Potebnja - Чала, Анна Геннадіївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
Materials articles reflect one of the pressing problems – clarify key concepts of bilingualism and bilingual education facing language education in modern educational space. The article analyzes the phenomenon of bilingual education in the context of the development of the modern world, basing on sociolinguistics studies Alexander Potebnja.